FINDING A PREDICTIVE VALUE FOR THE PAIN LEVEL OF ANTERIOR ADDUCTOR MUSCLE INJURIES BASED ON SOME BIOCHEMICAL MARKERS IN ATHLETES - Asst. Prof. Sahar Mohammed Salman (Scholars Digest Publishing, 2025)
Improper rehabilitation procedures frequently result in adductor anterior injuries being associated with various levels of pain. Athletes frequently encounter difficulties in regaining peak performance due to these programs, adversely affecting athletic efficacy and heightening the risk of relapses or recurrences. The primary objective of rehabilitation is to restore normal muscular function and to avert the recurrence of the injury. Consequently, the researcher observed a disparity among athletes regarding pain levels and the recurrence of discomfort associated with injuries to the anterior adductor muscle during the medical rehabilitation phase. She analyzed the case by assessing the contribution percentage of each biochemical sign during the injury period to ascertain the pain level. The researcher performed measurements on a sample of 24 injured individuals throughout 8 weeks of observation, monitoring, and evaluation. She determined that the correlation between the enzyme (CRP) and the pain level in the adductor muscle is the strongest, signifying that it serves as the most evident signal of the resurgence of sports-related pain levels. She advocated for the adoption of the predictive value determined during the assessment of the medical rehabilitation procedure.
Keywords: Pain level, adductor anterior muscle, biochemical parameters.